Measurement of Efficiency Levels in Open House System Broiler Breeders in Malang Regency, Indonesia - Stepanus Pakage; Budi Hartono; Bambang Ali Nugroho; Deny Anjelus Iyai; Alnita Baaka; Agustinus Gatot Murwanto; John Arnold Palulungan; Irba Unggul Warsono; Trisiwi Wahyu Widayati; Isti Widayati; Dwi Nurhayati; Noviyanti; Rizky Arizona; Purwaningsih; Elfira Kariane Suawa; Muhammad Affan Mu’in; Mohammad Jen Wajo; Sangle Y Randa; Djonly Woran (Faculty of Animal Science, Universitas Brawijaya, 2023)
Broiler farming in Malang Regency, East Java, Indonesia, has experienced rapid growth, significantly contributing to the regional economy. In this region, the open cage system is among the broiler cage systems that are commonly used. Therefore, this study aims to analyze 1) factors affecting growth, 2) factors causing technical inefficiency, and 3) technical, allocative, and economic efficiency. The results showed that factors such as day-old chicks (DOC), feed, and drugs positively affected broilers' development. However, there was a variation in the level of technical efficiency of 0.047 due to inefficient sources, which included the age of breeders, education level, work experience, number of family members, and employment status. Despite the variation in efficiency levels, the average breeder demonstrated high technical, allocative, and economic efficiency with values of 0.93, 0.99, and 0.92, respectively. This performance indicated that the average breeders had yet to reach peak efficiency but were categorized as high-efficiency. To further enhance productivity, broiler farming required additional DOC feed and adequate training for broiler breeders to maximize productivity and resource utilization. Based on these results, recommendations were made to provide loans to broiler farms with simple terms and conditions, specifically for purchasing DOC, feed, labor, medicines, and fuel.